(untitled) (Revista de Artes Marciales Asiáticas, 2017)
Introduction: Wushu Sanda is a mixed orientation combat sport in which athletes duel wearing red or black clothes. Despite its popularity, the knowledge about its technical and psychophysiological aspects are scarce. Objective: The aim of this study was to quantify the motor actions and the color bias and home advantage existence possibility in female matches from the 13th World Wushu Championships, held in Indonesia, 2015. Material and methods: In an observational study were analyzed 46 matches involving 55 athletes. Each match was analyzed twice, and were considered 22 possible techniques (5 types of punches, 5 types of kicks and 12 different throws). All the motor actions were registered for each athlete, aside of match outcome, clothing color and continent of origin. Results: From all applied motor actions, 48.2% were punches, 46.9% were kicks and 4.8% were throws. Athletes applied 11±8.67 punches, 10.7±5.63 kicks and 1.1±1.6 throws per round. The number of throwing techniques applied on the first and second rounds was higher in winners (F=10.24, p=0.002 and F=7.82, p=0.006 respectively). No differences were found in motor behavior among distinct competitive phases (F(3;88)=1.87; p=0.140; η2p=0.06). Home advantage was observed supporting Asian athletes (χ2=10.12, p=0.038). Color bias was observed supporting athletes who wore red (χ2=8.52, p=0.004), which won a higher number of matches (65%). Conclusions: To the detriment of grappling actions (throws), female international level Wushu Sanda athletes predominantly used striking motor actions (punches and kicks). Winners applied a higher number of throws than losers. Home advantage was observed supporting Asian athletes. Color bias was observed supporting female athletes who wore red.